Ancoragem nas decisões de consumo: evidências experimentais com discentes do curso de administração da Universidade Federal Rural do Semi-árido - Costa, Sandrelly Maria Prado (Universidade Federal Rural do Semi-Árido, 2018)
The assumption that people like it can be configured as heuristics that drive decision making, once the willing, was a motivation to make a verification of the heuristic of anchoring in consumer decisions. Methodology: Quantitative and qualitative, and applied through experiments. According to this objective, experiments were performed composed of 4 tasks in order to be ready to participate in the anchoring process: (i) in the ordering of decisions; (ii) whether the information is always to the product anchored the pricing; (iii) to be taken by incomplete calculations, or even to do so, to make the best cost-benefit decision; (iv) and the anchoring index (high, low and general) in the pricing.The results were observed to have participated as directed anchors as their choices according to their direction. You may have found the decisions according to the anchoring rules, just as the market measures are influenced by irrelevant anchors to the object, and by not performing full calculations causes decisions towards the anchor, and finally that the anchoring indices are extracted from the pricing of the sense of anchorage that is imposed on each group (high and low).
Monografia
Keywords: Finanças comportamentais; Tomada de decisão; Ancoragem; Racionalidade limitada; Consumo; Behavioral finance; Decision making; Anchoring; Bounded rationality; Consumption; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO